Assessment of physician's knowledge, perception and willingness of telemedicine in Riyadh region, Saudi Arabia - Ahmed I. Albarrak; Rafiuddin Mohammed; Nada Almarshoud; Lama Almujalli; Rawan Aljaeed; Sarah Altuwaijiri; Tahani Albohairy (Elsevier, 2021)
Introduction: Telemedicine is the utilization of computer applications and telecommunication technologies to deliver clinical services remotely. The Ministry of Health in Saudi Arabia, recently established an e-Health strategy that includes the use of telemedicine in order to improve the accessibility and quality of care among patients and healthcare providers. Objectives: The present study aimed to assess the knowledge and perception of telemedicine and its applications among physicians. Secondly, to evaluate their willingness towards adopting telemedicine in clinical practice. Methods: The study is a cross sectional conducted in four hospitals; King Abdulaziz Medical City, King Faisal Specialist Hospital and Research Center, King Saud Medical City and King Saud University Medical City in Riyadh, Saudi Arabia. The survey questionnaire was a self-administered, which was adopted from previous studies. The questionnaire consists of; access to a computer and its literacy, knowledge, perceptions and willingness of telemedicine. Results: A total of 391 physicians of which male (301; 77.0%) and female (90; 23.0%) completed the questionnaire. Half of the participants never used personal computers or laptops at home. Interestingly, 89.2% of them have two or more smart devices. Participants have average knowledge about telemedicine technology (46.1%). Nearly, 77% of the professionals believed that continuous training is necessary for the use of telemedicine (P = 0.01). The highest level of perception was (90%) for telemedicine as a viable approach for providing medical care services to patients. More than 90% of specialties professional agreed that telemedicine can save time, money and further believed information and communication technology (ICT) has a potential role in healthcare. Overall, 70% of physicians reported a very low number of conferences, speeches or meetings held regarding telemedicine technology in their working places. Main issues reported in adopting telemedicine are patient privacy, the high cost of equipment, lack of suitable training, and lack of consultation between information technology expert and clinicians. Conclusions: Despite the fact that the majority of professionals have two or more smart devices and are communicating with patients via email or social media. However, the majority of medical professionals still have low knowledge of telemedicine technology. In addition, most of the participants showed positive perceptions of telemedicine and are willing to adopt it in clinical practice. The major reported barriers for the adoption of telemedicine were privacy issues, lack of training, cost and issues related to information and communication technology.